2008
DOI: 10.1124/dmd.108.021527
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Drug-Drug Interactions: The Effect of Desvenlafaxine and Duloxetine on the Pharmacokinetics of the CYP2D6 Probe Desipramine in Healthy Subjects

Abstract: ABSTRACT:A number of antidepressants inhibit the activity of the cytochrome P450 2D6 enzyme system, which can lead to drug-drug interactions. Based on its metabolic profile, desvenlafaxine, administered as desvenlafaxine succinate, a new serotonin-norepinephrine reuptake inhibitor, is not expected to have an impact on activity of CYP2D6. This single-center, randomized, open-label, four-period, crossover study was undertaken to evaluate the effect of multiple doses of desvenlafaxine (100 mg/day, twice the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 30 publications
8
47
0
Order By: Relevance
“…80 In vitro data indicate that desvenlafaxine has negligible effect on CYP450 enzymes or on p-glycoprotein activity and, consequently, is believed to have a minimal likelihood of inducing drug interactions. [89][90][91] Gabapentin. Gabapentin is a c-aminobutyric acid analogue indicated for the treatment of partial seizures and postherpetic neuralgia.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…80 In vitro data indicate that desvenlafaxine has negligible effect on CYP450 enzymes or on p-glycoprotein activity and, consequently, is believed to have a minimal likelihood of inducing drug interactions. [89][90][91] Gabapentin. Gabapentin is a c-aminobutyric acid analogue indicated for the treatment of partial seizures and postherpetic neuralgia.…”
Section: Pharmacologic Optionsmentioning
confidence: 99%
“…To examine the clinical implications, the effects of DVS 100 mg and duloxetine 30 mg bid on plasma levels of desipramine were compared in healthy subjects in a randomized, open label, crossover study. 29 In comparison to desipramine alone, co-administration of duloxetine resulted in increases in AUC and C max of desipramine (122% and 63% respectively). These were signifi cantly greater than the increases observed with DVS co-administration (22% and 19%, respectively), suggesting that DVS is not a clinically signifi cant inhibitor of CYP2D6 activity.…”
Section: Pharmacodynamics and Pharmacokineticsmentioning
confidence: 99%
“…Phase I hepatic metabolism of desvenlafaxine appears to play a small role in its elimination, marked by metabolism to N,O-didesmethylvenlafaxine by the cytochrome P450 (CYP450) 3A4 pathway [5]. Because desvenlafaxine is primarily metabolized via glucuronidation, and clinical reports have shown that desvenlafaxine exerts minimal effects on the activities of the CYP450 enzymes or p-glycoprotein, the potential ability of other drugs to alter desvenlafaxine metabolism is low [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%